Устойчивость автоцистерны против заноса и опрокидывания при движении по кругу с поперечным уклоном - Kulakovskiy Борис; Maksimov Павел (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2010)
The analysis of stability is carried out of tank truck to the drift and the tilting in circular movement with the side rake of road. The action of forces on the tank truck during the movement on the turning is examined. The dependences of the maximum turning radius of the tank truck on the rate of movement, degree of filling, coefficient of adhesion of wheel and of the speed of controlled wheels are determined.